Evaluation and Characterization of Caryophyllene Nanoemulsion Preparations from Clove Oil (Syzigium aromaticum) - Eriska Agustin; Whilly Martavinus (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
The clove plant (Syzygium aromaticum) is a plant from the Myrtaceae family. Clove plants can be found in various countries, including Indonesia. The contents of the clove plant have been studied to have beneficial pharmacological effects, one of which is the caryophyllene content in the clove plant which has antioxidant, antibacterial, etc. activities. This research aims to create a formula and evaluate the physical characteristics of a karyophyllene nanoemulsion preparation from clove oil. The method for making nanoemulsion preparations is made into three formulas with varying concentrations of karyophyllene compounds as active substances, namely F0 (0%), F1 (0.5%), and F2 (1%). Evaluation of the preparation includes organoleptic tests, pH tests, particle morphology tests, stability tests, and nanoemulsion globule size tests. The results showed that the nanoemulsion preparations of caryophyllene compounds F0, F1, and F2 had globule sizes of 82 ± 1.45 nm, 95 ± 2.67 nm, 89 ± 1.46 nm on day 1, while on day 28 the globule sizes were 99±2.87 nm, 116±2.56 nm, and 121±1.56 nm. The nanoemulsion preparation is clear white, semi-thick, and has a distinctive aroma. The morphology of the nanoemulsion globules is spherical and homogeneous. All three nanoemulsion formulations demonstrated good physical stability, as indicated by the absence of precipitation, phase separation, and turbidity, as well as pH values within the acceptable range for nanoemulsion systems, despite a slight increase in globule size observed over the 28-day storage period.